1994
DOI: 10.1111/j.1751-1097.1994.tb05010.x
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Cytosine Excimer State: The Role of Geometry Optimization

Abstract: A study of the lowest excited dimer (excimer) singlet state of the DNA base cytosine was performed with fully optimized geometry (near the cis‐syn form) using a slightly modified version of MOPAC6 (AM1 hamiltonian) and 112 excited configurations involving an active space consisting of the four highest occupied and the two lowest empty MO of the dimer. A binding energy of 3 kcal/mol for the excimer state is demonstrated, and the excimer fluorescence is predicted to be shifted 150 nm to longer wavelengths relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Calculations aimed at understanding how excited states of nucleobase multimers depend on local structure are just beginning to appear [61][62][63][64], and these will help to resolve these issues. A few studies have even examined cytosine-cytosine base stacks [65,66], but have not yet used geometries from structural biology. Clearly, progress in understanding the electronic structure of these multichromophoric systems will be facilitated by calculations that incorporate realistic structural models.…”
Section: Structural Implicationsmentioning
confidence: 99%
“…Calculations aimed at understanding how excited states of nucleobase multimers depend on local structure are just beginning to appear [61][62][63][64], and these will help to resolve these issues. A few studies have even examined cytosine-cytosine base stacks [65,66], but have not yet used geometries from structural biology. Clearly, progress in understanding the electronic structure of these multichromophoric systems will be facilitated by calculations that incorporate realistic structural models.…”
Section: Structural Implicationsmentioning
confidence: 99%
“…Because of the slow rate of energy relaxation, these long-lived states associated to excimer-like states have been suggested as the precursors of the DNA photolesions, including photodimers. 3,9 On the other hand, Crespo-Hernández et al 10 have recently shown by using femtosecond transient absorption spectroscopy that excimers are formed in high yields in a variety of synthetic DNA oligonucleotides and conclude that excitedstate dynamics of A • T DNA is controlled by base stacking.…”
mentioning
confidence: 99%
“…The PEC for the ground state is repulsive at the closedshell Hartree-Fock and at the CASSCF͑12,12͒ level. Similarly, at the semiempirical level, employing the AM1 parameterization, 9 no stable excimer was found if the two molecules were constrained to be parallel, leading to a small binding energy ͑3 kcal/ mol͒ upon geometry optimization. The lowest singlet excited state becomes weakly bound at the CASSCF͑12,12͒ level.…”
mentioning
confidence: 99%
“…It has been shown that many DNA photolesions, including bipyrimidine photodimer, are formed from singlet excited-states. [1][2][3][4] Understanding the structure and properties of the initial excited singlet electronic state is essential in elucidating the photostable mechanism in DNA. Because of extremely short lifetimes of the singlet excited-states and complex combinations of several tautomeric forms of the base pairs, experimental studies on real DNA base pair are very difficult.…”
Section: Introductionmentioning
confidence: 99%